THE EFFECTIVENESS OF THE ANDROID BASED LINEAR LOCUS MEDIA ASSISTED PBL MODEL ON NARRATIVE TEXT READING COMPREHENSION SKILLS: EFEKTIVITAS MODEL PBL BERBANTUAN MEDIA LINARLOKUS BERBASIS ANDROID TERHADAP KEMAMPUAN MEMBACA PEMAHAMAN TEKS NARASI - Oliv Via Ani Ramadhana; Rani Setiawaty; Diana Ermawati (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This study was motivated by the low interest in reading among students, which has resulted in poor reading comprehension skills in narrative texts in elementary schools. This condition causes students to have difficulty identifying main ideas, understanding important information, and summarizing the content of the reading material in a coherent manner. The purpose of this study was to determine the difference in the average pretest and posttest scores and the effectiveness of the Android-based LINARLOKUS media-assisted PBL model in improving the narrative text comprehension skills of fourth-grade elementary school students. The method used was quantitative with a One Group Pretest–Posttest pre-experimental design. The research sample consisted of 35 fourth-grade students at SD 1 Jekulo, selected using a saturated sampling technique. Data were collected through pretest and posttest descriptive tests and documentation, then analyzed using the Shapiro–Wilk normality test, Paired Sample T-Test, and N-Gain. The results showed a significant difference between the pretest and posttest scores with a significance of 0.000 < 0.05. The average N-Gain score of 0.588 was in the moderate category with an effectiveness percentage of 58.8%, which was considered quite effective. Thus, it can be concluded that the PBL model assisted by LINARLOKUS media is quite effective in improving students' reading comprehension skills in narrative text material. The implications of this study provide recommendations for teachers to apply active, contextual learning and utilize Android-based media to increase students' interest and reading skills